Ethical Boundaries Of Artificial Intelligence Use In Academic Writing: A Study Among University Students - Muhammad Dzaky Nabil Al Ghani; Zidni Ma’ruf; M. Kurniawan Aries Akbar; Muhammad Akbar (Indonesian Journal of Educational Technology, 2026)
As Artificial Intelligence (AI) becomes increasingly common in higher education, worries regarding academic honesty and ethical standards have increased. This study intends to explore how university students view and apply ethical limits while utilizing AI tools for academic writing. A group of six undergraduate students at Politeknik Negeri Sriwijaya, who have experience using AI assistants, were interviewed through semi-structured interviews using a qualitative descriptive design. The study reveals that students perceive AI as a supporter of brainstorming, idea generation, and structural validation, rather than removing human intellect altogether. A clear ethical limit is established, and the use of AI is considered unethical if it necessitates unreviewed "copy-pasting" without personal input or comprehension. Also, it is observed that there is a significant amount of agreement among students regarding the necessity for disclosure on AI usage to uphold academic integrity. While this increase in efficiency is welcome, students are concerned that it could harm critical thinking skills and they are skeptical of AI accuracy, which must be closely monitored by humans. The report recommends that schools should establish distinct regulatory mechanisms and AI literacy initiatives to ensure the adherence to ethical AI.